Influence of Nd and Ce doping on the structural, optical and electrical properties of V2O5 thin films - Jassim, I. K. (Iraqi Journal of Physics, 2019)
Nano-structural of vanadium pentoxide (V2O5) thin films were deposited by chemical spray pyrolysis technique (CSPT). Nd and Ce doped vanadium oxide films were prepared, adding Neodymium chloride (NdCl3) and ceric sulfate (Ce(SO4)2) of 3% in separate solution. These precursor solutions were used to deposit un-doped V2O5 and doped with Nd and Ce films on the p-type Si (111) and glass substrate at 250°C. The structural, optical and electrical properties were investigated. The X-ray diffraction study revealed a polycrystalline nature of the orthorhombic structure with the preferred orientation of (010) with nano-grains. Atomic force microscopy (AFM) was used to characterize the morphology of the films. Un-doped V2O5 and doped with 3% concentration of Nd and Ce films have direct allowed transition band gap. The mechanisms of dc-conductivity of un-doped V2O5 and doped with Nd and Ce films at the range 303 K to 473 K have been discussed.